Identification of the allergenic proteins of litchi chinensis (Litchi) pollen: partial characterization and sensitivity test - Ranajit Kumar Shaha (2012)
The pollen of Litchi chinensis (Litchi) is an important aeroallergen of Bangladesh. The pollen of this fruits plant was collected from full bloomed flower growing in different places of Rajshahi, Bangladesh. Pollen protein extracted and partial purified by means of long-term PBS extraction, salting out, dialysis, gel filtrations and DEAE-Cellulose chromatography which was designated by LFPP (Litchi flowers pollen protein). Gel filtration of the partial purified pollen protein gives two main peaks. The major peak gives four bands on SDS-PAGE. After gel filtration and Ion exchange chromatography, a single band in the protein profile of LFPP, (M.W. 28 kDa) was the major allergenic component of Litchi chinensis (Litchi) flower pollen. The homogeneity and the molecular weight of the protein were estimated by SDS-PAGE, and Gel filtration was 28kDa. The allergenic protein was identified by skin test and shows the pectate lyase (Pel) activity. Skin-prick tests also revealed highest degree of sensitivity to the Nawabgang sample giving positive response in 90% of the patients. Skin reactivity ranged between 1+ and 3+.